Measures for Increasing Performance of the Rail Freight Transport in the North-South Direction - Eva Brumercikova; Bibiana Bukova; Iwona Rybicka; Pawel Drozdziel (Communications - Scientific letters of the University of Zilina, 2019)
The article elaborates on measures aimed at increasing the performance of the rail freight transport carried out in the north-south direction. The measures are designed based on the implemented analyses focused on the analysis of the current situation of international trade and development of international transport as well as the analysis of the current situation of the European transport infrastructure. The north-south direction was selected due to the enormous increase of the transit road transportation.